2014
DOI: 10.1002/jso.23757
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of laparoscopic low anterior resection in terms of local recurrence

Abstract: Local recurrence rates decreased with increasing surgeon experience, as did other short-term outcomes, especially in advanced disease cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…In addition, these factors might be associated with the surgeon's laparoscopic experience. The cut-off points of the learning curve for laparoscopic rectal cancer surgery have been shown to be based on the mean operative time (range, 50–90 cases) [25, 32, 33]. In our previous study, we demonstrated that the mean operative time was 240 min after performing 90 cases [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, these factors might be associated with the surgeon's laparoscopic experience. The cut-off points of the learning curve for laparoscopic rectal cancer surgery have been shown to be based on the mean operative time (range, 50–90 cases) [25, 32, 33]. In our previous study, we demonstrated that the mean operative time was 240 min after performing 90 cases [25].…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off points of the learning curve for laparoscopic rectal cancer surgery have been shown to be based on the mean operative time (range, 50–90 cases) [25, 32, 33]. In our previous study, we demonstrated that the mean operative time was 240 min after performing 90 cases [25]. Some investigators have insisted that operative time alone is insufficient as a surrogate marker for laparoscopic surgery [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients underwent radical proctectomy, including high ligation of the inferior mesenteric artery, total mesorectal excision, and en bloc resection of the adjacent involved organs . The interval between preoperative CRT and surgery was 6–8 weeks.…”
Section: Methodsmentioning
confidence: 99%